2008
DOI: 10.1103/physrevb.77.014440
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for strong magnon contribution to the TMR temperature dependence in MgO based tunnel junctions

Abstract: We have prepared MgO based magnetic tunnel junctions which show up to 143% tunneling magnetoresistance ͑TMR͒ ratio at room temperature and 205% at 12 K. This TMR temperature dependence is mainly caused by a strong temperature dependence in the antiparallel magnetic state, while in the parallel state the change of condunctance is small. We found that a modified version of the magnon excitation model may be applied to these MgO magnetic tunnel junctions. If the thermal smearing of the tunneling electron's energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 21 publications
6
44
0
Order By: Relevance
“…4 are for MTJs having almost identical nominal t MgO values of 2.66 nm ± 1% (Table I). Thus, the smearing effect of the Fermi distribution function at finite temperatures to the tunneling conductance [50,52,61] can be regarded as almost identical for these MTJs.…”
Section: Experimental Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…4 are for MTJs having almost identical nominal t MgO values of 2.66 nm ± 1% (Table I). Thus, the smearing effect of the Fermi distribution function at finite temperatures to the tunneling conductance [50,52,61] can be regarded as almost identical for these MTJs.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…Previous studies on MTJs with an amorphous AlO x tunnel barrier reported an increase in G P with increasing T up to room temperature [50,51]. Most of the epitaxial MTJs with an MgO or MgAl 2 O 4 tunnel barrier that have been reported so far have also shown an increase in G P [8,[52][53][54][55][56][57], while some epitaxial MTJs showed a decrease [58][59][60]. The increase in G P with T for MTJs, including epitaxial MTJs, has been mostly explained by spin-flip inelastic tunneling via a thermally excited magnon, i.e., the Zhang model with an evidence of the role played by magnons indicated by tunneling spectroscopy [51,52,56].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…13 It was recently shown that the temperature dependence of the TMR ratio of a Co 2 FeAl 0.5 Si 0.5 / MgAl 2 O x / CoFe TMJ followed a T 3/2 power law ͑T being the temperature͒, due to the thermal excitation of spin waves. 14 cussed in terms of the role of thermally excited magnons for spin-flip scattering 17 from the majority-spin band to minority spin gap states, including minority spin interface states, in the emitter electrode, and vice versa in the collector electrodes. 16,18 In this context, the knowledge of the exchange stiffness, which will largely determine the energy required to create a spin wave, is a crucial parameter that must be understood to gain insight into the construction of superior devices.…”
Section: Introductionmentioning
confidence: 99%